Teatro aula - aula teatro : el juego dramático en los niveles educativos - Alberti, Juan; Amuriza, Jon; Barta, Fernando; Carpente, Bernardo; Herans, Carlos; Izquierdo, María José (Acción educaiva, 1988)
Teatro y aula-- Aula y teatro